A case series review of patients with Thrombocytopenia and Absent-Radii syndrome (TARS) and their management during pregnancy. (17th November 2021) - Halperin, Daniel; Pavord, Sue; Myers, Bethan
Abstract: Bleeding diatheses due to platelet-related disorders can present challenges to treating clinicians, especially in the context of peri- and post-partum patients in the obstetric setting. Thrombocytopenia and Absent-Radii syndrome (TARS) is an inherited disorder characterized by reduced bone marrow platelet production, skeletal deformities affecting radii and other limbs; cardiac, renal, and other heterogeneous anomalies may occur. It is caused by the co-inheritance of a microdeletion and a nucleotide polymorphism in the RBM8A gene on chromosome 1. Bleeding phenotype is more severe than platelet numbers which might predict especially in infants but improves with age. There is minimal literature regarding the impact of pregnancy and puerperium. We describe the management of three pregnancies in the hematology-obstetrics clinic. As platelet counts normally decrease through pregnancy, close monitoring is required in TARS. No major bleeding was seen antenatally but two required platelet transfusions during labor. No other treatment definitely improves bleeding, although case reports of steroids claim variable success. Tranexamic acid may be helpful, and thrombopoietin agonists represent a potential future option.